Layanan Konseling Pranikah pada Calon Pengantin di Balai Penyuluh KB Kecamatan Ajung - Fasira, Ira; Adila, Khalisa; Ismail, Moh.; Iskandar, Robby Sofyan; Suryadi (UIN Kiai Haji Achmad Siddiq Jember, 2024)
This research focuses on pre-marital counseling services for prospective brides and grooms at the Family Planning Extension Center, Ajung District. This research uses a qualitative method from a phenomenological perspective. The research subjects were prospective brides and grooms who were about to get married and carried out counseling facilitated by the Ajung District Family Planning Counseling Institute. The types of data used in this research are primary data and secondary data. The research results show that the implementation of premarital counseling is carried out through information services, consultation services, individual counseling and group counseling. The premarital counseling material is the application of 8 family functions, preventing maternal and infant deaths with 4 too, and preventing stunting through optimizing 1000 HPK. Barriers to premarital counseling include counselees who tend to be passive, counseling facilities are inadequate and the average bride and groom do not know about premarital counseling, thus affecting the effectiveness of the implementation of premarital counseling